Resistance to Love in Medieval English Romance Negotiating Consent, Gender, and Desire - Piercy, Hannah (Studies in Medieval Romance, 2023)
This book explores resistance as a widespread motif in medieval romance to consider themes of consent, gender, and desire. Medieval romance is usually considered a genre that celebrates love, desire, and sexuality within marriage. However, moments of resistance within it offer a point of tension, where normative scripts and expectations are exposed and opened up to challenge. This book explores such resistance as a widespread motif in the genre, tracing the subversive possibilities it presents, and through them uncovering how romance constitutes particular kinds of love as desirable, shaped by intersecting factors, including gender, status, race, religion, and morality. Drawing upon contemporary work on consent, the politics of desire, and asexuality, it examines how resistance is often transformed into acceptance, through consensual negotiation or coercive force: the romances discussed here demonstrate that a certain level of force, pressure, and persuasion is accepted as a means of forming relationships within the genre, but this reliance on coercion reveals the effort to which romances must go to uphold normative structures of desire. Considering a variety of works, from Marie de France's twelfth-century Guigemar to Thomas Malory's Morte Darthur, Geoffrey Chaucer's Franklin's Tale to William Caxton's fifteenth-century prose romances, this book argues that romance teaches its readers what and whom to desire, as well as how to behave when negotiating their desires, and explores the wider implications for understanding consent, gender, and desire in medieval England. This book is available as an Open Access ebook under the Creative-Commons License CC-BY-NC-ND